2007
DOI: 10.1177/0963947007072847
|View full text |Cite
|
Sign up to set email alerts
|

The subconscious in James Joyce's `Eveline': a corpus stylistic analysis that chews on the `Fish hook'

Abstract: In James Joyce's short story, 'Eveline', a young woman is thinking about a new life away from an unhappy existence which involves caring for a violent father. In the story, Eveline is to elope with Frank to Buenos Aires, but Eveline fails to join him on the night boat. This story has attracted much critical attention. In particular, commentators have picked up on the faint clues throughout that Eveline is not going to leave her home. It is as though Eveline's subconscious is communicating this while she is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
1
12
0
1
Order By: Relevance
“…Skilfully written, Eveline and the rest of the stories in this anthology can be a material and springboard for teaching literature through linguistic means, an approach, which according to (Fowler, 1984), has been challenged by both literary critics and linguists. Eveline, being one of James Joyce's exemplar short stories in this anthology, has been considered remarkable by many scholars for its literary complexity (Attridge, 2004;Chatman, 1969;Culler, 1975;Hart, 1969;Leech & Short, 1981;O'Halloran, 2007;Short, 2006;Stubbs, 2005;Toolan, 2001). More so, the works of O'Halloran (2007) and Chun (2011) have confirmed that Eveline foregrounds processes that deal with inaction, deliberately presented in passive form as metaphors of paralysis, with thoughts, feelings, and recollections dominating the text-these characteristics have been confirmed in the foregoing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Skilfully written, Eveline and the rest of the stories in this anthology can be a material and springboard for teaching literature through linguistic means, an approach, which according to (Fowler, 1984), has been challenged by both literary critics and linguists. Eveline, being one of James Joyce's exemplar short stories in this anthology, has been considered remarkable by many scholars for its literary complexity (Attridge, 2004;Chatman, 1969;Culler, 1975;Hart, 1969;Leech & Short, 1981;O'Halloran, 2007;Short, 2006;Stubbs, 2005;Toolan, 2001). More so, the works of O'Halloran (2007) and Chun (2011) have confirmed that Eveline foregrounds processes that deal with inaction, deliberately presented in passive form as metaphors of paralysis, with thoughts, feelings, and recollections dominating the text-these characteristics have been confirmed in the foregoing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, corpus analysis has begun to be used to help support interpretation (and evaluation) of poetry and other literary genres (see, for instance, Adolphs and Carter, 2002;Biber, 2012;Culpeper 2009;Fischer-Starke, 2010;Hoover, 2002;Louw, 1993;Mahlberg 2007;McIntyre and Walker, 2010;O'Halloran, 2007aO'Halloran, , 2007bRomaine, 2010;Stubbs, 2005;Toolan, 2006). In this article, one of my uses of a corpus will be in this established sense, that is, to provide empirical support for interpretation.…”
Section: Supporting Interpretation With Corpus Evidencementioning
confidence: 99%
“…For examples of keyword studies of literary texts see e.g. Culpeper (2009), Scott and Tribble (2006), O'Halloran (2007), Toolan (2009. While the analysis of keywords is becoming increasingly popular in corpus linguistics, keyness can still be seen as "a new territory" and "there are problems in identifying exactly what the keyness procedure comes up with and determining the boundaries of the research endeavour" (Scott 2010: 43).…”
Section: Abstract and The Stylistician's Checklistmentioning
confidence: 99%